218k views
21 votes
The functions f and g are defined as follows.

3
f(x) = 2x° +6
g(x) = –2x+4
Find f(-3) and g(6).
Simplify your answers as much as possible.

The functions f and g are defined as follows. 3 f(x) = 2x° +6 g(x) = –2x+4 Find f-example-1

1 Answer

12 votes

Answer:

f(-3)= -48 g(6)= -8

Explanation:

the the numbers into the corresponding functions and simplfy following the order of operations which would look like this:

f(-3)=2(-3)^3 + 6

=2(-27)+6

=-54+6

f(-3)=-48

and

g(6)= -2(6)+4

= -12+4

g(6)= -8

Hope this helps! :)

User Otsaw
by
4.8k points